Draft Sixth Five year Plan (1980-85) and Annual Plan (1981-82) Volume I Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1980)
The state is essentially rural in character and its economy is basically agricultural. The level of overall development is, therefore, directly linked with the development of agriculture. The main thrust in the development of agriculture has been to increase the level of food production which is being actualized by bringing more areas under high yielding varieties, distribution of quality seeds, increase in off take of fertilizers bringing more areas under irrigation and by talking adequate protective measures against diseases and pests along with increasing production of vegetables, oil seeds and cash crops like Mushrooms, Saffron, Zira and potatoes. Considerable improvement has become in the use of in-puts which go to increase the productivity of land. The off-take of fertilize is which had decreased from 11,90 tones in 1973-74 to 18O tones in 1974-75 because of escalation in prices in view of oil crisis in the world has reached a level of 15,380 tones in 1977-78 as a result of timely measures taken by the Government.
Government of Jammu and Kashmir
Planning and Development Department Srinagar
Keywords: Agriculture and allied service; Agro Industries; Horticulture; Agrarian Reforms and Consolidation of Holding; Forest including Game Preservation; Investment in Agriculture Financial Institutions; Marketing; Agriculture Research and Education; Agriculture University; Seed Processing Plant; Manures and Fertilizers; Farmers Training